G (fx) = x + 1이고 g (x) = 3x-2이면 g [f (5)]?

G (fx) = x + 1이고 g (x) = 3x-2이면 g [f (5)]?
Anonim

대답:

# g (f (color (red) (5))) = 16 #

설명:

이 문제를 해결하려면 먼저 대체해야합니다. #color (빨강) (f (x)) # 또는 #color (빨강) ((x + 1)) # 매회마다 #color (빨강) (x) # 함수에서 #g (x) #.

#g (색상 (빨강) (x)) = 3color (빨강) (x) - 2 # 다음과 같이됩니다.

# 2 (색 (적색) (f (x))) = 3 (색 (적색) (x + 1)) - 2 #

# 2 (color (red) (f)) = (3xx color (red) (x)) + (3xx color (red) (1)

# g (color (red) (f (x))) = 3x + 3 - 2 #

# g (color (red) (f (x))) = 3x + 1 #

이제 해결할 # g (f (5)) # 우리는 대용해야한다. #color (적색) (5) # 각각 #엑스# …에서 # g (f (x)) #

#g (f (color (red) (x))) = 3color (red) (x) + 1 # 다음과 같이됩니다.

# g (f (color (red) (5))) = (3xxcolor (red) (5)) + 1 #

# g (f (color (red) (5))) = 15 + 1 #

# g (f (color (red) (5))) = 16 #

# "첫 번째,"f (x) = x + 1 rArr f (5) = 5 + 1 = 6. #

# g (x) = 3x-2 rArr g f (5) = g (6) = 3 (6) -2 = 18-2 =